The Use of Geographic Information Systems in Biodiversity and Conservation - Jones, Peter G.; Beebe, Stephen E.; Tohme, Joseph M.; Galwey, Nicholas W. (Springer, 1997)
We describe a method for applying geographical information systems (GIS) to exploring biodiversity in the wild relatives of crop species and illustrate its application to the wild common bean (Phaseolus vulgaris L.). We use the latitude, longitude and altitude of the location of origin of each accession in a germplasm collection of wild P. vulgaris, along with long-term monthly mean values of rainfall, temperature and diurnal temperature range for about 10000 stations throughout Latin America to produce maps indicating areas with ‘bean-favouring’ climates. In a test case, these identify a new suitable area in Colombia where wild P. vulgaris has been reported in the literature, and two more areas which are strong candidates on other grounds. Dividing the ‘bean-favouring’ climates into clusters identifies areas that have similar climates but are geographically remote, where we can expect to find wild beans with similar ecological adaptation. We discuss the implications of these results for conserving and improving the common bean, and the application of these methods to other species.